Microwave-Assisted Synthesis of Strontium Tungstate Particles by A Solid-State Metathetic Route - Sung Lim, Chang (Asian Journal of Chemistry, 2012)
Well crystallized strontium tungstate (SrWO4) particles were formed by a solid-state metathetic (SSM) route assisted by a microwave irradiation, showing a spherical and homogeneous morphology with sizes of 0.5-1 μm. The synthesized SrWO4 particles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy. The optical properties were investigated by photoluminescence emission and Raman spectroscopy. With excitation at 250 nm, the major peaks are located at the blue wavelength of 425-450 nm. The emission spectra of 4-8 narrow neighbored and sloped shoulders were considered to form by defects structure. The well-resolved Raman spectra for the SrWO4 particles at 920, 836, 798, 371, 334 and 235 cm-1 provide that the synthesized particles are highly crystallized.